2018
DOI: 10.1039/c7sc03765a
|View full text |Cite
|
Sign up to set email alerts
|

Achieving efficient photodynamic therapy under both normoxia and hypoxia using cyclometalated Ru(ii) photosensitizer through type I photochemical process

Abstract: A type I Ru(ii) photosensitizer retained an excellent PDT effect under hypoxia through the formation of highly-oxidative hydroxyl radicals under light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
150
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 233 publications
(151 citation statements)
references
References 53 publications
1
150
0
Order By: Relevance
“…79 The photocytotoxicity of complex 84 can be achieved by two-photon irradiation and under one-photon irradiation exhibits greater photocytotoxicity than complex 85. Subsequent cellular studies in HeLa cell monolayers after light treatment depict the relocalization of complex 84 toward the 86 Further work demonstrated that the complex is effective in tumor-bearing mice and inhibits growth of the tumor. Ruthenium(II)-based therapeutics have entered clinical trials, such as the three well-known ruthenium anticancer agents: NAMI-A, KP1019, and KP1339.…”
Section: ■ Therapeutic Luminescent Complexesmentioning
confidence: 99%
“…79 The photocytotoxicity of complex 84 can be achieved by two-photon irradiation and under one-photon irradiation exhibits greater photocytotoxicity than complex 85. Subsequent cellular studies in HeLa cell monolayers after light treatment depict the relocalization of complex 84 toward the 86 Further work demonstrated that the complex is effective in tumor-bearing mice and inhibits growth of the tumor. Ruthenium(II)-based therapeutics have entered clinical trials, such as the three well-known ruthenium anticancer agents: NAMI-A, KP1019, and KP1339.…”
Section: ■ Therapeutic Luminescent Complexesmentioning
confidence: 99%
“…[5][6][7][8] Although the details of the operation of type Im echanisms,e specially how O 2 is involved, are still under debate,m any studies have shown that type IPDT performs well even under low O 2 conditions and, consequently,that it might be the basis for the design of new approaches to overcome the limits of hypoxia in type II PDT. [72][73][74][75] In ar ecent investigation, Lv et al demonstrated that ac yclometalated Ru complex displays excellent type IP DT activity. [72] Ac oumarin group was covalently incorporated into this complex to increase its light-harvesting ability and also to enable it to serve as ag ood electron-donor.I nterestingly,t he complex (Ru2) displays ah igher killing effect on cancer cells than the coumarin-free analog.I na ddition, Ru2 shows ahigh photocytotoxic effect under hypoxia because of its ability to generate hydroxyl radicals.Invivo studies (drug dose,5 mg Kg À1 ;i njection way,i ntratumoral;d rug-light interval, 15 min;l ight conditions,2 05 mW cm À2 ,1 5min) indicate that Ru2 has aPDT effect on an endogenous hypoxic solid tumor as reflected in remarkable inhibition of tumor growth on the 14th day after treatment.…”
Section: Type Ip Dtmentioning
confidence: 99%
“…The results indicated that MnO 2 @PPAIB could generate a large amount of oxygen by decomposing H 2 O 2 in the acidic enviroment. Finally, to testify the generation of ROS in the presence of H 2 O 2 (100 × 10 −6 m ), MnO 2 @PPAIB and PPAIB in acidic or neutral H 2 O 2 solution were irridiated (660 nm, 3.6 mW cm −2 ) with a commercially available ROS probe 1,3‐diphenylisobenzofuran (DPBF) . As shown in Figure j, the PPAIB generated a small amount of ROS in acidic (pH = 6.5) or neutral (pH = 7.4) H 2 O 2 solution.…”
Section: Resultsmentioning
confidence: 99%